The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.28991/scimedj-2021-03-si-10
|View full text |Cite
|
Sign up to set email alerts
|

Second Wave Analysis and Confirmed Forecasts of the SARS-Cov-2 Epidemic Outbreak in São Paulo, Brazil

Abstract: Objective: A SEIR compartmental model was previously selected to estimate future outcomes to the dynamics of the Covid-19 epidemic breakout in Brazil. Method: Compartments for individuals vaccinated and prevalent SARS-Cov-2 variants were not included. A time-dependent incidence weight on the reproductive basic number accounted for Non Pharmaceutical Interventions (NPI). A first series of published data from March 1st to May 8, 2020 was used to adjust all model parameters aiming to forecast one year of evolutio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…1b confirms the forecasts reported many months earlier, presenting the consequences of maintaining or empirically release the NPIs over specific time periods. 7 As the result, the average fitting value to confirmed cases (logarithmic scale) for the whole study period presents standard deviation SD = 0.097 and root mean square RMS = 0.11. By the end of the study period, the official number of confirmed cases reached 10.6 Million an increase of 2.5 folds on the population-based sample (4.2 Million), with 9% deviation under the predicted average value.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…1b confirms the forecasts reported many months earlier, presenting the consequences of maintaining or empirically release the NPIs over specific time periods. 7 As the result, the average fitting value to confirmed cases (logarithmic scale) for the whole study period presents standard deviation SD = 0.097 and root mean square RMS = 0.11. By the end of the study period, the official number of confirmed cases reached 10.6 Million an increase of 2.5 folds on the population-based sample (4.2 Million), with 9% deviation under the predicted average value.…”
Section: Discussionmentioning
confidence: 78%
“…The methodology employed in this work was presented in a previous publication, and illustrated in a flowchart diagram 7 . Such a methodology was applied to forecast the COVID-19 outbreak in S. Paulo, the largest populated city in Brazil, selected as a first reliable cohort study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations